Do internal medicine interns practice etiquette‐based communication? A critical look at the inpatient encounter. Issue 11 (12th October 2013) - Block, Lauren; Hutzler, Lindsey; Habicht, Robert; Wu, Albert W.; Desai, Sanjay V.; Novello Silva, Kathryn; Niessen, Timothy; Oliver, Nora; Feldman, Leonard
Abstract : Etiquette‐based communication may improve the inpatient experience but is not universally practiced. We sought to determine the extent to which internal medicine interns practice behaviors that characterize etiquette‐based medicine. Trained observers evaluated the use of 5 key communication strategies by internal medicine interns during inpatient clinical encounters: introducing one's self, explaining one's role in the patient's care, touching the patient, asking open‐ended questions, and sitting down with the patient. Participants at 1 site then completed a survey estimating how frequently they performed each of the observed behaviors. A convenience sample of 29 interns was observed on a total of 732 patient encounters. Overall, interns introduced themselves 40% of the time and explained their role 37% of the time. Interns touched patients on 65% of visits, asked open‐ended questions on 75% of visits, and sat down with patients during 9% of visits. Interns at 1 site estimated introducing themselves and their role and sitting with patients significantly more frequently than was observed (80% vs 40%, P < 0.01; 80% vs 37%, P < 0.01; and 58% vs 9%, P < 0.01, respectively). Resident physicians introduced themselves to patients, explained their role, and sat down with patients infrequently during observed inpatient encounters. Residents surveyed tended to overestimate their own practice of etiquette‐based medicine. Journal of Hospital Medicine 2013;8:631–634. © 2013 Society of Hospital Medicine